Effects of plyometric training on physical performance and mental well-being in young soccer players - Hammami, A.; Hammami, R.; Mahmoudi, A.; Rebai, H.; Saez-Berlanga, A.; Gene-Morales, J.; Juesas, A.; Colado, J. C. (Journal of Sports Sciences, 2025)
Plyometric training (PT) improves performance in young soccer players, but its psychological effects remain underexplored. This is especially relevant for young elite players facing early selection pressures. The aim was to evaluate the effects of unilateral and bilateral PT on performance and mental well-being in elite young soccer players according to their maturation level. Sixty-seven tier-3 male athletes (12.03±2.34 years; pre- and post-peak heigh velocity groups) were randomised into unilateral PT (n= 23), bilateral PT (n= 23), or active control (n= 21), with all groups maintaining standard soccer training. PT was delivered twice weekly over 8 weeks. Physical outcomes included 20-m sprint, Y-Balance Test, 15-m change-of-direction with ball. Psychological outcomes were somatic and cognitive anxiety and self-confidence measured using the CSAI-2 outside of a competitive context. Non-parametric ANCOVA (Quade) adjusted for maturity and anthropometry showed that unilateral PT induced the greatest improvements in sprint (np2 = 0.42), balance (np2= 0.27), and CoD (np2= 0.35), particularly in post-PHV players. Both PT groups reduced cognitive (np2 = 0.34) and somatic anxiety (np2= 0.41), with unilateral PT post-PHV showing the largest effects. Self-confidence increased (np2= 0.22), correlating with balance and sprint improvements. These findings support the use of maturity-specific PT to enhance both performance and mental status in young soccer.